2023
DOI: 10.1055/s-0042-1757411
|View full text |Cite
|
Sign up to set email alerts
|

Coagulase-Negative Staphylococci in Neonatal Blood: How Concerning?

Abstract: Objective Coagulase-negative staphylococci (CoNS) are being implicated as one of the leading causes of bloodstream infection (BSI). To study the spectrum, prevalence, and antimicrobial susceptibility of CoNS causing BSI in neonates. Materials and Methods A cross-sectional study was done in level III neonatal intensive care unit (NICU). Blood samples in automated culture bottles were processed as per the standard technique. Previously validated methods were followed for the characterization of CoNS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…17 In contrast, in the pediatric population, methicillin resistance was found to be 70% in the present study, which is very similar (70%) to that reported by Ansari et al, ranging from 40% to 100% among various CoNS species. 18 None of the isolates in the present study showed resistance to vancomycin and linezolid which was similar to previous studies, 19,20 where vancomycin-resistant CoNS detection was performed on various clinical isolates and nasal samples respectively.…”
Section: Discussionsupporting
confidence: 90%
“…17 In contrast, in the pediatric population, methicillin resistance was found to be 70% in the present study, which is very similar (70%) to that reported by Ansari et al, ranging from 40% to 100% among various CoNS species. 18 None of the isolates in the present study showed resistance to vancomycin and linezolid which was similar to previous studies, 19,20 where vancomycin-resistant CoNS detection was performed on various clinical isolates and nasal samples respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Such invasive infections caused by coagulase-negative staphylococci typically proceed less aggressively than those caused by Staphylococcus aureus, and are more prolonged over time. However, in recent years, they have become of increasing clinical importantance [10,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%